Analisis Kepuasan Pelanggan Berdasarkan Kualitas Pemipilan, Harga Jasa, dan Teknologi Mesin serta Kelayakan Finansial Usaha Pemipilan Jagung Mas Anugerah Klobot di Kabupaten Ogan Komering Ulu Timur - Denny Yudha Alexander Tampi; Singgih Santoso (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2026)
This study aims to analyze the factors influencing customer satisfaction in mechanized corn-shelling services and to assess the financial feasibility of the Mas Anugerah Klobot enterprise in East OKU Regency. Using a quantitative approach, data were collected from 50 customers and 15 seasonal workers through Likert-scale questionnaires. Regression results indicate that shelling quality, service pricing, and machine technology positively affect customer satisfaction, with pricing and technology emerging as the strongest predictors. These findings highlight the importance of processing speed, accuracy of results, and affordability in shaping customer perceptions. In addition to customer satisfaction, the financial analysis using Payback Period, IRR, NPV, and Profitability Index (PI) confirms that the enterprise is economically feasible. The business also provides important social benefits for the church, particularly in empowering congregation members’ economic well-being. It creates seasonal employment opportunities, increases household income, and strengthens the church’s role as an agent of community empowerment. Thus, the enterprise contributes not only to economic gains but also to improving the welfare and independence of the church community.